The secret war of Julia Child : a novel - Chambers, Diana R. (Sourcebooks Landmark, 2024)
"Before she mastered the art of French cooking in midlife, Julia Child found herself working in the secrets trade in Asia during World War II, a journey that will delight both historical fiction fans and lovers of America's most beloved chef, revealing how the war made her into the icon we know now. Single, 6 foot 2, and thirty years old, Julia McWilliams took a job working for America's first espionage agency, years before cooking or Paris entered the picture. The Secret War of Julia Child traces Julia's transformation from ambitious Pasadena blue blood to Washington, DC file clerk, to head of General "Wild Bill" Donovan's secret File Registry as part of the Office of Strategic Services. The wartime journey takes her to the Far East, to Asia's remote front lines of then-Ceylon, India, and China, where she finds purpose, adventure, self-knowledge - and love with mapmaker Paul Child. The spotlight has rarely shone on this fascinating period of time in the life of ("I'm not a spy") Julia Child, and this lyrical story allows us to explore the unlikely world of a woman in a World War II spy station who has no idea of the impact she'll eventually impart"--